Seeing the Role of PCK and TPACK from the Perspective of Science Education Researchers in 2018-2020: What's Next? - Habibah Khusna Baihaqi; Jumadi Jumadi; Rizki Zakwandi (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2021)
The aim of this paper is portraying PCK and TPACK study by science education researchers’ perspective in 2018-2020 so that it can be used as support, theoretical background or clue for the next researcher who interested on this framework. Content analysis used as method for this qualitative study. Subjects are 25 open access articles that published in Journal of Teacher Education, Teaching & Teacher Education, and etc. The result shows PCK and TPACK still be one of urgent and loved research by three continents, they are America. Europe, and Asia. We divided the topic as 2 part, 5 themes for PCK, and 3 themes for TPACK. Themes for PCK are the need for professional knowledge of science teachers, relationships among PCK components, PCK as a theoretical background, examining PCK, and development of PCK. Themes for TPACK are TPACK used as theoretical background, interconnection among domain of TPACK, and development of TPACK.